Rocket Propellant Comparison: Conventional Planetary Mixing and Resonant Acoustic Mixing. Issue 1 (14th May 2021) - Smith, Paul C.; Huf, Joel P.; Williams, Christopher A.
Abstract: A standard HTPB/AP/Al composite rocket propellant formulation was prepared with a conventional vertical planetary action mixer and resonant acoustic mixer (RAM). Ingredients and process conditions were standardised as much as possible to facilitate a direct comparison of the two process regimes. Cured propellant specimens were characterised for sensitiveness, ballistic properties and mechanical properties at 3 temperatures (−54 °C, 25 °C and 74 °C). No significant differences were noted for sensitiveness between the planetary and RAM mixes. A slightly lower burn rate at 1000 psi (6.89 MPa) was noted for the RAM mixes. Maximum stress results at 25 °C were similar but significant differences in maximum strain and modulus were recorded. Maximum strain for the 1 Pint, 2 Gallon and RAM were 7.4 %, 9.1 % and 17.6 %, respectively. Modulus results were 26.0 MPa, 19.3 MPa and 11.1 MPa, respectively. Similar improvements in strain capability for the RAM propellant were recorded at −54 °C and 74 °C, with increases of 66 % and 117 %, respectively. A greater strain capability results from stronger interfacial adhesion between the solid fill and the binder, which is in turn generally a result of improved wetting of solid particles. This result, therefore, indicates more thorough mixing in the case of the RAM process but this requires confirmation through a more direct examination of the underlying mechanism. Abstract :